The seasonal occurrence of Well's syndrome. (March 2016) - Mokhtari, Fatemeh; Rezabakhsh, Aysa; Cheraghi, Omid; Ranjkesh, Mohammad; Rahbarghazi, Reza
Abstract Well's syndrome, in many circumstances, is determined by intensive eosinophilic infiltration into dermal layer with the clinical presentation of erythematous and edematous plaques which can easily be remitted by current corticosteroid therapies. Up to now, different etiologies have been proposed governing Well's pathophysiological procedure. Of note, no evidence of seasonal association has been already reported. A 70-years-old afebrile male presented with a chief complaint of 30-years history of cutaneous manifestations along with non-ulcerated edematous, erythematous plaques and patches, and extensive pruritus confined on both dorsal and palmar surface of upper extremities occurred annually in early summer. We hereby report a case in season-dependent of Well's syndrome occurrence.